Multiplexed Proximity Biotinylation Coupled to Mass Spectrometry for Defining Integrin Adhesion Complexes. Issue 1 (24th August 2020) - Chastney, Megan R.; Lawless, Craig; Humphries, Martin J.
Abstract: BioID, a proximity biotinylation technique, offers a valuable approach to examine the interactions occurring within protein complexes that complements traditional protein biochemical methods. BioID has various advantages that are beneficial to the study of complexes, including an ability to detect insoluble and transient proteins. We have applied BioID to the study of integrin adhesion complexes (IACs), which are located at the junction between the plasma membrane and actin cytoskeleton. The use of multiple BioID baits enables a complex‐wide, spatial annotation of IACs, which in turn facilitates the detection of novel proximal interactors and provides insights into IAC architecture. This article describes the labeling and affinity purification of IAC‐proximal proteins and their analysis by label‐free quantitative mass spectrometry. The article also outlines steps to identify high‐confidence proximity interactors, and to interrogate the topology and functional relevance of proximity interaction networks through bioinformatic analyses. © 2020 The Authors. Basic Protocol 1 : Proximity biotinylation of integrin adhesion complex components Basic Protocol 2 : Mass spectrometry data processing by MaxQuant and detection of high‐confidence proximal interactors Basic Protocol 3 : Bioinformatic analysis and data visualization